2017
DOI: 10.1117/1.jmi.4.3.031204
|View full text |Cite
|
Sign up to set email alerts
|

Survey on impact of regulations on radiation safety and development of radiation safety culture in 25 countries

Abstract: The purpose of this work was to assess the: (a) impact of regulations on radiation safety and development of radiation safety culture, (b) perceived safety level in the participating facilities, (c) future needs regarding strengthening of regulations, patient dose consideration, and exposure tracking, in different countries around the world. Appropriate questionnaires probing the above-mentioned themes were sent to radiologic professionals working in healthcare facilities. A total of 257 responses from 25 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A multinational study in 25 countries in Africa, Asia, and Europe suggested regulations have an impact on enhancing the radiation safety culture and a relatively high level of use of regulatory tools. 4 Skornik, however, noted in 2001 that most of the African countries were in the process of developing regulatory infrastructure. For example, 20 countries had a radiation protection law in force or in the final stage of its promulgation.…”
Section: Introductionmentioning
confidence: 99%
“…A multinational study in 25 countries in Africa, Asia, and Europe suggested regulations have an impact on enhancing the radiation safety culture and a relatively high level of use of regulatory tools. 4 Skornik, however, noted in 2001 that most of the African countries were in the process of developing regulatory infrastructure. For example, 20 countries had a radiation protection law in force or in the final stage of its promulgation.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of an IMS for radiation safety varies across countries [ 61 , 62 ]. Some nations have established self-sufficient IMS, primarily due to their development or launch of peaceful nuclear reactors.…”
Section: Reviewmentioning
confidence: 99%